The Effect Of The Use Of Wordless Picture Books In Improving Emotional Intelligence Of Children Age 5-6 Years In Paud Terpadu Lab Belia Semarang - Fitriana, Febi; Windiarti, Rina (Jurusan PGPAUD FIP UNNES, 2018)
Problems in early childhood that occurs in early childhood education institutions, especially group of TK B in PAUD Terpadu Lab Belia Semarang is found that the percentage amount is very much in the low category of emotional intelligence of children and has never been applied media wordless picture books. The research problem is Is media use wordless picture books can improve emotional intelligence in children aged 5-6 years in early childhood Belia Integrated Lab. The purpose of this study was to determine the increase emotional intelligence in children aged 5-6 years in early childhood Semarang Belia Integrated Lab in terms of the application of wordless picture books. This study aims to determine the increase in emotional intelligence in children aged 5-6 years at the PAUD Terpadu Lab Belia Semarang in terms of the application of Wordless Picture Books. This study uses the Pre-Experimental Design method with the One Group Pretest Posttest Design approach. The sample is students of kindergarten group B aged 5-6 years as many as 30 children. The sampling technique in this study is the purposive sample technique. Data collection techniques are observation and Likert scale. The data shows an increase in the mean value of 103.30 to 129.20, resulting in an increase in score of 25.9. Based on the results of calculations using Paired Sample t-Test obtain the value of -ttable> -tcounts> ttable, that is (-2,042>-16,160 or 16,160>2,042) with the value of Sig. (2-tailed) <0.05 which means there is a difference between the pretest and posttest values. The conclusions are that Ha is accepted and Ho is rejected, meaning that there is an increase in emotional intelligence through Wordless Picture Books for children aged 5-6 years in PAUD Terpadu Lab Belia.